2016
DOI: 10.1186/s40529-016-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses of Heteropogon contortus to drought stress in a dry-hot valley

Abstract: Background Heteropogon contortus is a valuable pasture species that is widely used for vegetation restoration in dry-hot valleys of China. However, to date, its morphological and physiological responses to drought, and the underlying mechanisms are not well understood. This study was aimed to investigate the morphological and physiological changes of H. contortus under drought stress during the dry-hot season. Heteropogon contortus was planted in pots and subjected to four levels of soil water treatments: abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…and Themeda triandra Forssk. are distributed throughout the tropics, and from Africa to East Asia, respectively, and are keystone species in many grasslands where they are found (Goergen & Daehler, 2001;Wang et al, 2016). The remaining species have variable range distributions from restricted to regionally widespread, mainly distributed throughout South Asia, Southeast Asia and Australia (Deshpande, 1988;Veldkamp, 2016;POWO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and Themeda triandra Forssk. are distributed throughout the tropics, and from Africa to East Asia, respectively, and are keystone species in many grasslands where they are found (Goergen & Daehler, 2001;Wang et al, 2016). The remaining species have variable range distributions from restricted to regionally widespread, mainly distributed throughout South Asia, Southeast Asia and Australia (Deshpande, 1988;Veldkamp, 2016;POWO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that red clover and timothy were more susceptible to drought and excess moisture stress when heavily fertilized with N. Bahrani et al [23] and Wang et al [24] have indicated that drought treatments cause a reduction in plant height. According to Chai et al [25] post-drought recovery of perennial grasses depended on the recovery of existing leaf tissue and the regeneration of new tissue from crowns, stolons and roots.…”
Section: Productivity Of Forage Grassesmentioning
confidence: 58%
“…Each of these changes may be related to altered biomass or nutrient allocation within a species in response to drought, and/or a drought‐induced change in species dominance. Within species, plants that experience water stress often have greater root‐to‐shoot ratios or deeper roots than well‐watered plants (Fernández & Reynolds, 2000; Huang, 1999; Skinner & Comas, 2010; Wang et al, 2016). In semi‐arid environments, drought also tends to increase the C:N ratio in leaves, thus decreasing litter quality (Sardans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within species, plants that experience water stress often have greater root-to-shoot ratios or deeper roots than well-watered plants (Fernández & Reynolds, 2000;Huang, 1999;Skinner & Comas, 2010;Wang et al, 2016). In semi-arid environments, drought also tends to increase the C:N ratio in leaves, thus decreasing litter quality (Sardans et al, 2012).…”
Section: Implications For Drought-induced Dominance Shiftmentioning
confidence: 99%
See 1 more Smart Citation